Impact of preoperative biliary drainage on postoperative complications and prognosis after pancreaticoduodenectomy: A single-center retrospective cohort study - Wang, Dong; Lin, Huajun; Guan, Chengjian; Zhang, Xiaodong; Li, Peixin; Xin, Chenglin; Yang, Xiaobao; Feng, Zhewen; Min, Yiyang; Gu, Xiaozhe; Guo, Wei (Frontiers in Oncology, 2022)
Background and objectives Obstructive jaundice is common in patients with pancreaticobiliary malignancies. Preoperative biliary drainage (PBD) can alleviate cholestasis; however, no consensus has been reached on the impact of PBD on the incidence of surgery-related complications and patient survival. This study aimed to evaluate the effect among patients treated with PBD. Methods This retrospective study examined the clinical and follow-up prognostic data of 160 patients with pancreaticobiliary malignancies who underwent pancreaticoduodenectomy (PD) at Beijing Friendship Hospital, Capital Medical University, from January 2016 to July 2020. Outcomes were compared between patients who underwent PBD (PBD group) and those who did not (control group). Changes in biochemical indicators were evaluated before and after drainage in the PBD group. Between-group differences in inflammatory indicators after PD were assessed using the Wilcoxon signed-rank test. Postoperative complications were classified according to the Clavien-Dindo classification system. The effects of PBD and biliary drainage efficiency on postoperative complications were evaluated using the chi-square test and binary logistics regression. The Kaplan-Meier analysis was used for between-group comparison of survival analysis. Univariate and multivariate regression analyses were performed to identify prognostic factors of survival. Results Total 160 patients were enrolled,the mean age of the study sample was 62.75 ± 6.75 years. The distribution of pancreaticobiliary malignancies was as follows: 34 cases of pancreatic head cancer, 61 cases of distal bile duct cancer, 20 cases of duodenal papilla cancer, 39 cases of duodenal ampullary cancer, and 6 cases of malignant intraductal papillary mucinous neoplasm (IPMN). PBD was performed in 90 of the 160 patients, with PBD performed using an endoscopic retrograde cholangiopancreatography (ERCP) approach in 55 patients and with percutaneous transhepatic cholangiography (PTC) used in the remaining 35 cases. The mean duration of drainage in the PBD group was 12.8 ± 8.8 days. The overall rate of complications was 48.05% (37/77) in the control group and 65.55% (59/90) in the PBD group with non-significant difference (χ2 = 3.527, p=0.473). In logsitics regression analysis, PBD was also not a risk factor for postoperative complications OR=1.77, p=0.709). The overall rate of postoperative complications was significantly higher among patients who underwent PBD for >2 weeks (χ2 = 6.102, p=0.013), with the rate of severe complications also being higher for this subgroup of PBD patients (χ2 = 4.673, p=0.03). The overall survival time was 47.9 ± 2.45 months, with survival being slightly lower in the PBD group (43.61 ± 3.26 months) than in the control group (52.24 ± 3.54 months), although this difference was not significant (hazard ratio (HR)=0.65, p=0.104). Conclusion In patients with malignant biliary obstruction, PBD does not affect the incidence of postoperative complications after pancreaticoduodenectomy nor does it affect patient survival. Prolonged biliary drainage (>2 weeks) may increase the incidence of overall postoperative complications and severe complications.